ANALYSIS OF INTERNAL CONTROL SYSTEMS AGAINST RECEIVABLES AND CREDIT SALES AT PT. JUI SHIN INDONESIA MEDAN BRANCH - ISKANDAR, RIZAL (Journal of Financial Management & Accounting, 2024)
The purpose of implementing the internal control system in the sales department is to ensure that all sales and sales results have been recorded correctly and can be billed while the internal control system in the accounts receivable section, aims to generate an immediate and accurate bill on the sales transactions that have been made. PT. Jui Shin Indonesia Medan Branch is one of the companies in Sumatra Island which is engaged in the trading of Ceramic and Granite. The company makes credit sales to face competitors, increase sales and increase profits. This is one of the factors that causes the high level of bad debts. The research method used in this research is descriptive method. Data collection techniques come from observation, interviews and documentation studies. The results of this study indicate the internal control system of credit sales at PT. Jui Shin Indonesia Medan Branch is quite good because the credit provision has been authorized in advance by the authorities, namely the branch manager so that the sales department cannot at will give credit to customers. Internal debt control system at PT. Jui Shin Indonesia Medan Branch is quite good because there is already a separation of the functions of sales, billing and receipt of collection results, and each transaction has also been supported by complete documentation and has used computerization so that each part will verify the bills paid by the customer. Keywords: Internal Control Systems, Receivables and Credit Sales.